(untitled) (The Pakistan Development Review, 2023)
In the wake of devolution of education to provinces through the 18th Constitutional Amendment, there has been a noticeable increase in public spending on school education. Moreover, certain reforms have been introduced in education planning, management and monitoring. These measures have enhanced availability of physical infrastructure and reading and writing material for schools and improved education monitoring. There is also evidence of marginal improvements in overall literacy rate and reading and arithmetic skills. Notwithstanding the limited gains, the reforms and increased public spending have not translated into commensurate improvements in schooling and learning outcomes. Analysis of proximate causes indicates that learning outcomes are not improving because the various elements of education system are not aligned around the goal of learning. In contrast, expansion of schooling appears to have remained a strategic objective of education delivery but it hasn’t experienced significant improvement either because of the existence of serious policy incoherence among various elements of education system. Prevalence of centralised, politically-influenced, discretionary and outdated planning and management practices combined with ineffectiveness of accountability mechanisms across the education delivery chain have undermined the effectiveness of well-intended reforms. A deeper exploration of these issues through the “political settlement” lens reveals that education outcomes aren’t recording major improvements because elite interest is aligned neither with the goal of learning nor access. Instead, elite interest is aligned more around patronage politics. Short-term, clientelist, political objectives govern education provision, owing to the highly fragile, exclusive, fragmented and personalised nature of political settlement. The predatory nature of political settlement has adversely affected both the design and implementation of reform initiatives.